Gaussian Generalized Woodall Numbers - , Orhan Eren, Yuksel Soykan (Archives of Current Research International, 2023)
In this work, we define and investigate Gaussian generalized Woodall numbers in detail, and focus on four specific cases: Gaussian modified Woodall numbers, Gaussian modified Cullen numbers, Gaussian Woodall numbers, and Gaussian Cullen numbers. We present some identities and matrices related to these sequences, as well as recurrence relations, Binet’s formulas, generating functions, Simpson’s formulas, and summation formulas.